A Quantitative Study Conducted in Nampula, Mozambique, Examined the Prevalence and Determinants of Anxiety and Depression among Health Sciences Students - Pires , Paulo Henrique das Neves Martins; Miranda , Guida de; Bambamba , Joel; Iacamurima , Regina; Bambamba , Angela; Mupueleque , Martins (Advanced Concepts in Medicine and Medical Research Vol. 10, 2023)
Introduction: Anxiety and depression are the most prevalent mental disorders in the world, close to 50% of the international disease burden due to psychiatric disorders and substance use. Research with university students show psychiatric disorders ‘rates around 15 to 25%. This chapter highlights the prevalence as well as determinants of the two major mental health diseases among health science students. It estimates anxiety and depression prevalence rates in Faculty of Health Sciences’ students, at Lúrio University in Nampula, Mozambique, and associated determinants, during the Covid-19 pandemic. Students experience mental health stress and interfere with their higher education very often due to their creating biased training environments and unfavourable life condition. Population’ depressive disorders prevalence is around 7%, but these disorders’ incidence increased due to the SARS-CoV-2 pandemic, impairing individual’s functional and psychosocial lives, and increasing the risk of major depressive disorder if not recognized and treated. Descriptive study, (21) cross-sectional quantitative, applying an indirect questionnaire from August to October 2020 to a students’ universe enrolled at the FHS of UniLúrio in Nampula, during the year 2020: 1,050 students. To have a representative sample, the number was calculated with a 95% confidence interval and a margin of error of 5%, considering the estimated prevalence (unknown) equal to 50%, obtaining 282 subjects. The selection of the sample was based on the students' accessibility to the digital questionnaire on their smartphone, as well as on their voluntary participation, aged 18 years or over, enrolled in the courses of Dentistry, Medicine, Nursing, Nutrition, Pharmacy, and Optometry, who attended the first to sixth year of graduation and who signed an Informed Consent Form (ICF). The Faculty of Health Sciences students’ random sample in Nampula answered the survey from August to October 2020, in a declared Public Calamity period due to Covid-19 pandemic. Results were analysed with Statistic Package for Social Science with a confidence interval of 95% and an error margin of 5%, using Q2 test to determine statistically significant associations. In the study, 276 students answered the survey, 50% of each gender, aged from 17 to 51 years, 60% coming from Nampula province, showing high rates of anxiety, depression and co morbidity, respectively 42.3, 34.3 and 25.9%, with a statistically significant association with bad relationships with friends, not enough sleep, trauma, lost and family antecedents. Conclusion: We confirmed the high prevalence of mental disorders in the Mozambican population, probably aggravated by governmental restrictive measures due to SARS-CoV-2 pandemic, implementing distance digital learning. FHS students have high prevalence rates of anxiety (42%) and depression (34%), mental disorders impacting patient – health student relation, limiting academic achievement and quality of life. These disturbances are accentuated by an insufficient amount of sleep (RR>2), low BMI, poor interpersonal relationships or traumatic or family history, as expected. The Covid-19 pandemic may have aggravated the incidence of these disorders. These results are important to allow the University to launch preventative activities and to promote therapeutic options, to grant the teaching–learning system success.